2016
DOI: 10.1111/1748-8583.12095
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐level effects of high‐performance work systems (HPWS) and employee well‐being: the mediating effect of organisational justice

Abstract: In this cross-level study, we examine the mediating influence of employee perceptions of the fairness of human resource practices associated with the high-performance work systems model. Data were collected from 187 employees in three companies in Ireland. Using cross-level analyses, employee perceptions of distributive, procedural and interactional justice were found to mediate the relationship between high-performance work systems and job satisfaction, affective commitment and work pressure. The findings als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
214
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(254 citation statements)
references
References 76 publications
(106 reference statements)
9
214
1
9
Order By: Relevance
“…Datta et al () defined HPWSs as a coherent set of “HR practices designed to enhance employees' skills, commitment, and productivity in such a way that employees become a source of sustainable competitive advantage” (p. 136). Following Heffernan and Dundon (), HPWSs include practices of “(a) sophisticated selection and training, (b) behaviour‐based appraisal, (c) contingent pay, (d) job security and (e) employee involvement” (p. 212). Experienced‐HPWSs represent individuals' awareness of the degree to which HPWS practices are actually implemented (Aryee et al, ; Liao et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Datta et al () defined HPWSs as a coherent set of “HR practices designed to enhance employees' skills, commitment, and productivity in such a way that employees become a source of sustainable competitive advantage” (p. 136). Following Heffernan and Dundon (), HPWSs include practices of “(a) sophisticated selection and training, (b) behaviour‐based appraisal, (c) contingent pay, (d) job security and (e) employee involvement” (p. 212). Experienced‐HPWSs represent individuals' awareness of the degree to which HPWS practices are actually implemented (Aryee et al, ; Liao et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Finally, this study was performed in the relatively under‐researched culture of China. Most research on the negative effects of HPWSs has been performed in Western countries and regions, including the Netherlands (Kroon et al, ), Sweden, and Finland (Ehrnrooth & Björkman, ); Wales (Jensen et al, ); and Ireland (Heffernan & Dundon, ). We hope that our findings extend the generalisability of the theory to examine the paradoxical mechanisms of HPWSs in an Asian culture.…”
Section: Introductionmentioning
confidence: 99%
“…By differentiating between happiness and health-related well-being we build upon recent studies on HRM and well-being (e.g. Heffernan & Dundon, 2016), which have demonstrated that HRM practices might have contradictory effects on both types of well-being (Van De Voorde et al, 2012). This research is conducted in a Long-Term Care setting in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Although the links between progressive human resources (HR) practices and firm performance resemble more of a 'black box', due to the various factors that mediate the relationship (Chowhan, 2016;Hefferman and Dundon, 2016;Jiang et al, 2013), it is largely acknowledged that 'high road' HR practices may be correlated with positive organisational outcomes. Hence, the HPWS literature suggests that certain work practices have positive effects on individual and group productivity, because they improve, among others, the organisational climate, motivation, employee empowerment, loyalty and commitment, and lower turnover rates, (Camps and Luna-Arocas, 2009;Shin and Konrad, 2014;Tregaskis et al, 2013).…”
Section: Workplace Practices and Productivitymentioning
confidence: 99%